REUNIFIKASI DUA KOREA DALAM PERSPEKTIF HUKUM INTERNASIONAL - Muhammad Yusuf Habibie (BELLI AC PACIS, 2020)
This research examines the problem of implications in Korea Peninsula reunifications. How its implications are reviewed from the perspective of international law on the State parties in international treaties and the status of membership in international organizations. This research is prescriptively normative legal research. The secondary data type includes source material primary law and secondary one. Data collection techniques using the study of librarianship and the law instruments which are Vienna Convention 1969 on the Law of Treaties and the Vienna Convention 1978 on the State Succession in respect to Treaties, further technical analysis using deductive method. The results showed the sequence of the Korea Peninsula was originally a single country, then it separated at the end of World War II and then Korean War broke out until the peace realized. Along with peace efforts, also carried out by reunification effort. From the state unification proccess, resulted the fusion of two Koreas named United Korea. The implications that arise from the perspective of States parties in international treaties is if there is an existing and relevant treaties it will continue to apply its relationship with successor state or other parties, and all treaties valid in the whole regions of the successor state. Reviewed from the perspective of membership in the international organization, the new State should be eligible following the beginning procedure to be accepted as a new member in the international organizations.